PENERAPAN MODEL PENGAJUAN DAN PEMECAHAN MASALAH (JUCAMA) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 30 LUBUKLINGGAU - Wahyuni, Mutia; Lucy Asri Purwasi; Novianti Mandasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the completeness of social studies learning outcomes for Class IV Students of SD Negeri 30 Lubuklinggau after implementing the Submission and Problem Solving (JUCAMA) Learning Model. This research method is experimental, with the design used being a one-group pretest-posttest design. The population in this study consisted of three classes, namely classes IVA, and IVB, and the sample in this study was 21 students class IVA students at SD Negeri 30 Lubuklinggau using random sampling technique. The data collection technique uses an essay test. Data analysis techniques use: t test. Based on the results of the t-test analysis with the confidence level obtained α= 0.05, the data = 2,460 and = 2,085, the data shows that the value of >. The students' average pretest score was 24,52 and the average posttest score was 76,79, so it can be said that a was accepted and o was rejected. The results of the research can be concluded that the social studies learning outcomes for Class IV of SD Negeri 30 Lubuklinggau after implementing the Submission and Problem Solving (JUCAMA) learning model are significantly complete.